Remarks on the adjustment of the poor rate taxation in Ireland - Stoney, Sadlier (Statistical and Social Inquiry Society of Ireland, 1851)
While it is the fashion of all classes of individuals at the present day, and for the last few years, as far back as I can call to memory, to rail at the taxation imposed on them by the government of our country, to complain of its pressure, and to call aloud for its reduction; some seem entirely, and others partially, to forget that without these taxes and duties our government cannot exist, or cannot afford us that security for our lives and properties which we now enjoy, in a degree superior to all other countries in the world.
Read February 18th 1850
Keywords: Taxation; Poor rate; 314.15